Relationship between teacher autonomy in foreign language under an ICT environment - Wei, Li (Panpacific University : [s.n.], 2020)
This study explore the extent of Chinese private HEI's English teacher autonomy(TA) and learners autonomy(LA), the extent of their ICT literacy, examined the difference between TA and LA in college English education given ICT literacy as a moderator variable, and then explored the correlation between teacher/learner autonomy and teacher/learner ICT literacy, In this study, the descriptive quantitative research method was adopted. Questionnaires were floated to 72 teachers and 334 students. Weighted mean, standard deviation, independent samples t-test, elaboration methods and Product Moment Correlation Coefficient were the statistical tools employed in the study. The research was conducted in two private HEI's (SYU & SXU) in Jinan, Shandong Province, China. The results of the study show that both teachers and students have an overall GOOD level of autonomy, specifically, teachers have EXCELLENT autonomous consciousness, are GOOD in autonomous capability and cooperation with others, but are offered FAIR autonomy-supportive environment. Students have EXCELLENT autonomous consciousness, but display FAIR level in autonomous capability, autonomy-supportive environment and cooperation with others. The overall extent of ICT literacy for both teachers and students are GOOD, while students are fair in ICT knowledge and skills. There is a significant difference between TA and LA, and TA is significantly higher than LA. There is no significant difference between TA and LA when their ICT literacy is POOR or EXCELLENT. However, there is a significant difference between TA and LA when their ICT literacy is FAIR or GOOD. Furthermore, teachers/learner autonomy has a significant positive correlation with teacher/learner ICT literacy. Finally, an action plan to promote TA, LA and their ICT literacy is proposed.
References: pages 120-134.
CHED-La Union
Keywords: Computer literacy